2019
DOI: 10.7554/elife.42646
|View full text |Cite
|
Sign up to set email alerts
|

Retinal stem cells modulate proliferative parameters to coordinate post-embryonic morphogenesis in the eye of fish

Abstract: Combining clonal analysis with a computational agent based model, we investigate how tissue-specific stem cells for neural retina (NR) and retinal pigmented epithelium (RPE) of the teleost medaka (Oryzias latipes) coordinate their growth rates. NR cell division timing is less variable, consistent with an upstream role as growth inducer. RPE cells divide with greater variability, consistent with a downstream role responding to inductive signals. Strikingly, the arrangement of the retinal ciliary marginal zone n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…RSCs within the teleost CMZ remain proliferative throughout the lifespan of the animal 3,55,56 and Dnmt1 is known to be required for cell cycle progression within stem cells of various tissue types 24,25,57 . Based on the significant loss of RSCs in dnmt1 -/larvae between 3-5dpf ( Figure 1) and the inability of dnmt1 -/-RSCs to maintain expression of cell cycle genes ( Figure 4), we hypothesized that dnmt1 -/-RSCs would be defective in their proliferative capacity.…”
Section: Loss Of Dnmt1 Activity Results In Decreased Rsc Proliferationmentioning
confidence: 99%
“…RSCs within the teleost CMZ remain proliferative throughout the lifespan of the animal 3,55,56 and Dnmt1 is known to be required for cell cycle progression within stem cells of various tissue types 24,25,57 . Based on the significant loss of RSCs in dnmt1 -/larvae between 3-5dpf ( Figure 1) and the inability of dnmt1 -/-RSCs to maintain expression of cell cycle genes ( Figure 4), we hypothesized that dnmt1 -/-RSCs would be defective in their proliferative capacity.…”
Section: Loss Of Dnmt1 Activity Results In Decreased Rsc Proliferationmentioning
confidence: 99%
“…Retinal ganglion cells are early-developing neurons in vertebrate retinas that express SHH, which promotes retinal progenitor proliferation and differentiation toward neuronal cell types ( Esteve and Bovolenta, 2006 ). Further, retinas in some animals grow by the addition of new neurons from a growth zone at the retinal margin ( Moshiri et al, 2004 ; Tsingos et al, 2019 ). Although this region is not involved in mouse and human development, it is part of their retinas ( Bhatia et al, 2009 ): progenitor expansion can be experimentally stimulated and involves SHH signaling ( Moshiri and Reh, 2004 ; Moshiri et al, 2004 , 2005 ; Bhatia et al, 2009 ; Christ et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the different types of CMZ cells can be generally distinguished by different sets of molecular markers, lineage tracing of individual CMZ cells over time has confirmed the lineage relationship between them in vivo. Early transplantation studies [ 46 , 47 ] and, more recently, genetic-based lineage mapping [ 26 , 41 , 42 , 48 ] have shown that according to its spatial organization, the CMZ is indeed composed of both RSCs and RPCs. Continuously labelled clones tracked over time in the growing eye of teleost fish form characteristic labelled ‘stripes’ of displaced cells demarcating their origin and destination along the clone [ 41 , 46 , 48 ].…”
Section: Distinct Cell Types Within the Cmz Niche And Their Proliferative And Multilineage Potentialmentioning
confidence: 99%
“…Early transplantation studies [ 46 , 47 ] and, more recently, genetic-based lineage mapping [ 26 , 41 , 42 , 48 ] have shown that according to its spatial organization, the CMZ is indeed composed of both RSCs and RPCs. Continuously labelled clones tracked over time in the growing eye of teleost fish form characteristic labelled ‘stripes’ of displaced cells demarcating their origin and destination along the clone [ 41 , 46 , 48 ]. Two different types of stripes/patches are commonly observed, including those that continuously label from the CMZ all the way into the central retina, termed arched continuous stripes (ArCoSs) [ 41 , 46 , 48 ], and those that label smaller stripe in the central retina that have become disconnected from the CMZ, termed ‘terminated patches’ [ 48 ] ( Figure 2 B).…”
Section: Distinct Cell Types Within the Cmz Niche And Their Proliferative And Multilineage Potentialmentioning
confidence: 99%